Retrospective assessment of animal welfare in cashmere-wearing goats by determining fiber cortisol: Retrospective assessment of animal welfare in cashmere-wearing goats by determining fiber cortisol (Veterinary Science, 2025)
Hair cortisol is useful as a biomarker for assessing stress, as the fiber can accumulate it through uptake into hair follicle cells from the blood and through local production. Goats with a double-coated fleece have coarse fibers that grow in summer–autumn and partially and asynchronously shed in spring; and fine fibers that grow until April–May, shed between June–September, and molt visibly in spring. Its collection by combing is repetitive, difficult to optimize, and questioned from an animal welfare standpoint. Shearing includes the entire fleece and exposes the animal to the environment. The aim was to evaluate the usefulness of cortisol measurement in fiber as a retrospective indicator of animal stress, and to compare the levels obtained from the average post-shearing population with those from non-invasive handling. Creole goats under semi-extensive conditions in La Pampa were shorn in mid-November, sampled by trichotomy in February of the following year, and in a subsequent cycle in May. Fiber cortisol was determined by an automated method by comparing the base and tip of the fiber with the post-shearing population data. Cortisol levels were significantly (p < 0.05) lower at the base of the fiber compared to the post-shearing mean, while no differences were found at the tip. This suggests that the stage following shearing involved higher stress compared to a later stage with lower physiological load. This difference supports the use of alternative fiber collection methods in a non-invasive way, promoting animal welfare.
Keywords: Goats, Animal fiber, Shearing, Stress, Biomarker